Needed adaptations in psychological treatments for people with vision impairment: A Delphi study, including clients, relatives, and professionals - Braakman, Jessica; Sterkenburg, Paula Sophia (Frontiers in Psychology, 2023)
Objective In this study, we aimed to identify the themes that should be addressed when adapting mental health treatments for adults with a visual impairment. Method A Delphi study was conducted among 37 experts, including professionals, persons with a visual impairment, and relatives of clients with a visual impairment. Results The Delphi consultation revealed seven categories (factors) that were identified as important in the treatment of mental health problems for clients with a visual impairment: the visual impairment, environment, stressors, emotions, the professional’s role and attitude, treatment setting, and accessibility of materials. Factors regarding the clients’ visual impairment, such as the severity of the impairment, influence the extent to which adjustments are needed in treatment. During treatment, the professional plays an important role in explaining any visual elements that a client with a visual impairment may miss. Conclusion In psychological treatment, clients require individual adaptations for their specific visual impairment.